2020
DOI: 10.1111/ajo.13244
|View full text |Cite
|
Sign up to set email alerts
|

Lipiodol flush under ultrasound guidance in Australia

Abstract: Infertility, the inability to conceive after one year of unprotected intercourse, 1 affects between 8-12% of couples worldwide. 1 The assessment of tubal patency under imaging is a necessary step in the investigation and treatment of infertility. 2 This can occur under radiologic guidance, referred to as hysterosalpingography (HSG), or under ultrasound guidance called hystero-salpingo contrast sonography (HyCoSy). Although a diagnostic procedure, several studies have shown improved pregnancy rates directly fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Our study adds to that of Sekhon et al 18 . in supporting Lipiodol flush under ultrasound guidance as a viable alternative to HSG, and is the first study to compare the sonographic visibility of Lipiodol to agitated saline in vivo .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our study adds to that of Sekhon et al 18 . in supporting Lipiodol flush under ultrasound guidance as a viable alternative to HSG, and is the first study to compare the sonographic visibility of Lipiodol to agitated saline in vivo .…”
Section: Discussionsupporting
confidence: 60%
“…16 It has been demonstrated ex vivo in model pelvises that agitated Lipiodol is visible with ultrasound imaging and can be sonographically visualised as well as, or even better than, WBCM. 17 Sekhon et al 18 have recently demonstrated that in patients with confirmed tubal patency with WBCM at HSG, ultrasound-guided Lipiodol flushing of the tubes is a safe and effective alternative to tubal flushing with OBCM at the time of HSG. This is a retrospective observational study to report the feasibility and tolerability of performing Lipiodol flushing at the time of tubal patency assessment with HyCoSy.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid-soluble contrast media may be preferred to increase the chances of pregnancy [17]. However, because of concerns that lipid-soluble agents remain in the ovarian tubes for a long time [18], water-soluble contrast agents have recently begun to be used in radiographic examination [36]. In the present study, the agent type was not investigated.…”
Section: Implications For Clinicians and Parentsmentioning
confidence: 98%
“…In the study evaluating the effects of such treatment modification, it was shown that, similarly to the classic HSG, 51% of patients became pregnant after administering oil contrast under ultrasound control within six months. During the procedure, the patients experienced only moderate discomfort, and the procedure was characterized by a high safety profile (Sekhon et al, 2020). The oil contrast may be additionally shaken before administration or given to turbulent flow to create fine air bubbles that significantly improve visualization during ultrasound (Zen et al, 2020).…”
Section: The Therapeutic Effect Of Oil Contrastmentioning
confidence: 99%